La sátira en la red social facebook estudio de caso "korreo - Heredia Miles, Alisson Nayely (Machala, 2023)
Humor and manipulation have become the other side of information in the wake of the internet's growth, particularly in the realm of entertainment. Laughter and fictional information are the keys to understanding the type of culture that society tends to consume. Most digital media nowadays operate differently from traditional media, creating satirical content that has become the new way to satirize within social networks. In this way, satire has taken new directions. In this current research, the aim is to investigate satire on the Facebook social network, with a case study "Korreo." The analysis focuses on the digital page "Korreo" of Facebook. The methodology applied in this research work corresponds to a mixed approach, using probabilistic analysis and experimental field design to obtain the intended results.
El humor, la manipulación se han convertido en la otra cara de la información tras el crecimiento del internet, en concreto el entretenimiento, con la risa y la información ficticia son la clave para entender el tipo de cultura que la sociedad acostumbra a consumir, la mayoría de los medios digitales en la actualidad se manejan de forma diferente a los medios de comunicación tradicionales creando contenido satírico la cual se ha convertido en la nueva forma de satirizar dentro de la redes sociales, de esta manera la sátira ha tomado nuevos rumbos. En esta presente investigación, tiene la finalidad de investigar la sátira en la red social de Facebook estudio de caso “Korreo” tomando como estudio del análisis a la página digital “Korreo” en Facebook, la metodología que se va aplicar en esté trabajo de investigación corresponde al enfoque mixto a través del análisis probabilístico a través del diseño de campo experimental para obtener los resultados planteados.
Keywords: FAKE NEWS; DESINFORMACION; FACT-CHECKING; HUMOR MANIPULABLE.